Lepidic-predominant adenocarcinoma of the lung in an elderly cat with kidney failure - Urquiza-Bravo, Odette; Ledesma, Nestor; Morales, Elizabeth (Brazilian Journal of Veterinary Pathology, 2024)
A long-haired, male, neutered domestic cat was referred to a veterinary clinic for the first time at 13 years of age due to anorexia, vomiting, dehydration, and depression. Blood biochemistry revealed renal azotemia. The cat was only given food for animals with kidney failure, and no treatment was given. Three weeks before its death at 16 years of age, the clinical signs returned, becoming more frequent and intense. The cat was referred to the veterinary clinic again, and also severe hypertension and mild dyspnea as the unique respiratory signs were detected. Blood biochemistry again revealed renal azotemia. At necropsy, the lungs exhibited a nodule in the right caudal lobe with a 3-cm-long axis and another nodule in the left caudal lobe with a 2-cm long axis, which histologically corresponded to a lepidic-predominant adenocarcinoma. The bronchioalveolar origin of the neoplasms was corroborated by immunohistochemistry with specific biomarkers, namely Thyroid Transcription Factor-1 (TTF-1), Napsin A, Surfactant Protein B (SP-B), Pancytokeratin and Vimentin, with the neoplastic tissue testing positive for all biomarkers. Both kidneys presented macroscopic and microscopic lesions consistent with nephritis and severe fibrosis, which was deemed to be the cause of death. Primary lung neoplasms in cats are rare and difficult to detect clinically due to clinic signs that may be nonspecific.